1991
DOI: 10.1007/bf01933179
|View full text |Cite
|
Sign up to set email alerts
|

Parallel defect control

Abstract: How can small-scale parallelism best be exploited in the solution of nonstiff initial value problems? It is generally accepted that only modest gains inefficiency are possible, and it is often the case that ldquofastrdquo parallel algorithms have quite crude error control and stepsize selection components. In this paper we consider the possibility of using parallelism to improvereliability andfunctionality rather than efficiency. We present an algorithm that can be used with any explicit Runge-Kutta formula. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To obtain the coefficient γ m , we apply the Maclaurin Series in (4). Recall that the Maclaurin Series is the Taylor Series expansion of a function about 0.…”
Section: Derivation Of Off-step Point Methodsmentioning
confidence: 99%
“…To obtain the coefficient γ m , we apply the Maclaurin Series in (4). Recall that the Maclaurin Series is the Taylor Series expansion of a function about 0.…”
Section: Derivation Of Off-step Point Methodsmentioning
confidence: 99%
“…Recalling that the 15 digits experiments reported in [7] indicate that a minimal spacing of 0.2 is acceptable in the case of Hermite interpolation, we expect that on 15-digit computers and for orders up to p = 10, an averaged spacing of 2/(p + 2) should be acceptable in the case of the more stable Lagrange interpolation formulas. We remark that the optimal location of the off-step points for defect control as derived in [7] is in the interval where the defect is to be computed, rather than advancing the current step point as in (2.12).…”
Section: On the Choice Of Abscissas A;mentioning
confidence: 95%
“…Probably, the most realistic option is a limitation on the minimal spacing of the abscissas ai. In [7] where Hermite interpolation formulas were used for deriving reliable error estimates for defect control, it was found that on a Silicon Grafics Inc. Power Iris 4D /240S-64 machine with 15 digits precision, the abscissas should be separated by 0.2 in order to suppress rounding errors. For the more stable Lagrange interpolation formulas, we expect that slightly smaller spacings are still acceptable.…”
Section: On the Choice Of Abscissas A;mentioning
confidence: 99%
See 2 more Smart Citations